Prosorhynchoides lamprelli n. sp. (Digenea: Bucephalidae) from the brassy trevally, Caranx papuensis (Teleostei: Carangidae), from off Lizard Island on the Great Barrier Reef, Australia - Bott, Nathan J.; Cribb, T. H. (Zootaxa, 2005)
Prosorhynchoides lamprelli n. sp. (Digenea: Bucephalidae) is described from the intestine of the brassy trevally, Caranx papuensis (Carangidae) from off Lizard Island, Great Barrier Reef, Australia. The new species is differentiated from other species of Prosorhynchoides Dollfus, 1929 by the shape and distribution of its vitelline follicles, the shape and extent of its uterus and the configuration of its digestive system. This is the first bucephalid to be described from Caranx papuensis; we have not encountered this species from other carangids or from over 1,500 individuals of other teleosts species we have found to be infected with bucephalids from the Great Barrier Reef.